Field tests on model efficiency of twin vertical axis helical hydrokinetic turbines. (15th May 2022) - Zhang, Aiming; Liu, Sen; Ma, Yong; Hu, Chao; Li, Zhengyu
Abstract: Twin vertical axis helical hydrokinetic turbines (VAHHTs) are a type of renewable energy conversion device that can generate electricity from the kinetic energy of free flowing water. To optimize its hydrodynamic performance, a typical twin VAHHTs model with a NACA0020 blade profile, diameter ( D ) of 0.2 m, height ( H ) of 0.45 m, solidity ratio ( σ ) of 0.38, and enwinding ratio ( ϖ ) of 1.25 was tested. Based on the controllable open channel velocity, a test platform was built to study the effect of different rotational direction, spacing, inflow direction, and phase difference on the efficiency of twin VAHHTs. The results show that the torque measurement platform can accurately measure the torque ( T ), water velocity ( V ), and rotational speed ( ω ) simultaneously. When the rotational direction of the twin VAHHTs is not outward opposite (-+), the efficiency is more than 9.52% higher than that of a single VAHHT. The efficiency increases first, and then decreases with an increase of the spacing between the two turbines. The change of inflow direction angle has a large influence on the efficiency of the twin VAHHTs. The initial phase difference has little effect on the performance of the twin VAHHTs. The highest average efficiency of the twin VAHHTs is 0.2315, which is 10.24% higher than that of a single VAHHT. The results supplement the deficiencies of the measured data at high velocity and provide validation for the numerical calculation of the efficiency of twin VAHHTs. Highlights: Field tests on model efficiency of twin helical turbines are carried out. The test can synchronously measure torque, water velocity, and rotational speed. The influence of the factors on the efficiency of twin helical turbines is tested. The efficiency of the twin helical turbines is 10.24% higher than that of single.